The Role Of Viral Marketing In Purchasing Decision-Making Of The Syrian Consumer (A Field Study On The Pioneers Of Social Networking Sites In Lattakia Governorate) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of this research is to study the role of viral marketing in purchasing decision-making among Syrian consumers represented by pioneers of social networking sites in Lattakia Governorate, where five social networking sites were chosen: Facebook, Twitter, Instagram, YouTube, and WhatsApp, within the framework of knowing the impact of marketing activity through which to make the purchasing decision. This study relied on the analytical descriptive approach. An electronic questionnaire was designed for the purpose of collecting primary data. It was distributed to a random sample of 88 consumers of social networking sites in Lattakia Governorate. The collected data was then analyzed and hypotheses tested using the SPSS.25 program. The study reached a set of results, the most important of which was the existence of a statistically significant relationship between viral marketing via social networking sites (Facebook, Twitter, Instagram, YouTube, WhatsApp) on the one hand, and the purchasing decision-making of the Syrian consumer represented by the pioneers of social networking sites in Lattakia Governorate on the other hand. It was found that the strongest semantic relationship was between viral marketing and purchasing decision-making via Facebook, followed by Twitter, then WhatsApp, then YouTube, and finally Instagram.